Zjazdy książąt śląskich z 1327 roku - Ptak, Marian J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In the political and legal history of Silesia, 1327 is regarded as a breakthrough year owing to the establishment of fealty ties between the King of Bohemia and a group of local Piast dukes. This began a process in which all Silesian dukes eventually became vassals, while some duchies and their parts were taken over by the Bohemian king, who became their direct ruler. This testified to a gradual break of political and legal ties between the Silesian duchies and Poland and its king, with the ties between the Silesian dukes and the Bohemian king and Kingdom of Bohemia becoming increasingly strong. As a result, Silesia became one of the countries that made up the Crown of St. Wenceslaus. So far the literature on the subject has focused on individual acts of fealty of the dukes and the king, but has not mentioned that they took place during congresses held for the purpose. Congresses of Silesian dukes had a long tradition going back to the second half of the 12th century. Three such congresses were held in 1327: in Opava 18–19 February, featuring at least four Upper Silesian dukes, Duke of Opava, King of Bohemia and a group of Bohemian lords; in Bytom 24 February, probably featuring the same participants; and in Wrocław 5–11 April with participants including the Duke of Wrocław and the Duke of Opole, the estates of the Duchy of Wrocław, i.e. the local nobility and towns, the clergy with the papal nuncio in partibus Polonie and some superiors of Wrocław monasteries, as well as a delegation of the Wrocław Jews. The structure of the 1327 Wrocław congress has all the fundamental marks of a Silesia-wide assembly of estates, later referred to as Fürstentag ducal assembly. This places in a new light the origins and chronology of Polish parliamentarism.
Keywords: Śląsk; książęta śląscy; zjazdy książąt; zgromadzenie książęce